Deportacje do obozów zagłady w Bełżcu i Auschwitz-Birkenau ludności żydowskiej z getta krakowskiego w relacjach ofiar - Zajączkowska-Drożdż, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The author of this article describes the history of Krakow Ghetto and presents in detail the occurrences taking place since its establishment to dismantlement. Particular emphasis is put on the deportation of Jewish population to extermination camps in Belzec and Auschwitz-Birkenau. The article is based primarily on original sources i.e. on publications and accounts of those who witnessed these events. Krakow Ghetto was established on the 3rd of March 1944 in order to concentrate local Jewish population and to separate it from the rest of society. The borders of the ghetto were firmly closed and guarded. People who found themselves in the ghetto were used and exploited to labor for the occupying force. The elderly, the children and those deemed useless for the Germans were promptly murdered in extermination camps. Deportation actions in Krakow Ghetto started with the selection process aimed at choosing those bound for transport. The victims were assembled on the Zgoda Square and led to the train station in Plaszow where they were put aboard trains heading for extermination camps in Belzec or Auchwitz-Birkenau. The accounts included in the article concern three deportation actions of Jewish population to extermination camps. The first deportation happened in June of 1942; the next one in October of the same year. The deportees were transferred to Belzec extermination camp and executed there. The next deportation was connected with the process of ghetto’s dismantlement, taking place on the 13th and 14th of March 1943. All those selected for transport were hauled to Auchwitz-Birkenau and murdered there.
Keywords: deportations; Jews; extermination of Jews; extermination camp; Belzec; Auschwitz; Birkenau